Nature and chemical abundances of a sample of Lyman-α emitter objects at high redshift - Dors, Oli L. (2018)
We built a grid of photoionization models and compiled already available observational emission line intensities (1000 < λ(Å) < 2000) of confirmed star formation regions and Active Galactic Nucleus (AGNs) in order to classify five Lyα emitter (LAE) objects at high redshift (5.7 < z < 7.2). We selected objects for which at least one metal emissionline was measured. The resulting sample is composed by the objects RXCJ2248.7-4431-ID3, HSC J233408+004403, COSY, A1703-zd6, and CR7 (clump C). The photoionization models were built assuming a Power Law (associated with the presence of an AGN), a Direct Collapse Black Hole (DCBH), and Population II stars for the ionizing source. The resultingmodels were then compared with observational emission-line ratios in six diagnostic diagrams to produce a spectral classification of the sample.We found that CR7 (clump C),HSC J233408+004403 and COSY probably have a non thermal ionizing source (AGN or DCBH) while the RXC J2248.7- 4431-ID3 and A1703-zd6 seem to host a stellar cluster. Detailed photoionization models were constructed to reproduce observational emission line ratios of the sample of LAEs, and to derive chemical abundances and number of ionizing photons Q(H) of these objects. From these models, we found metallicities in the range 0.1 ≲ (Z/Z⊙) ≲ 0.5 and logQ(H) > 53. Values for C/O abundance ratio derived for the LAEs seem to be consistent with those derived for local star forming objects with similar metallicities, while an overabundance of N/O was found for most of the LAEs.